Stimulating learning by empowering leadership: Can we achieve cross-level creativity simultaneously?. Issue 8 (7th November 2016) - Li, Mingze; Zhang, Pengcheng
Abstract : Purpose: The purpose of this paper is to answer the theoretical and practical calls for an examination of the multi-level effects of empowering leadership on creativity. In addition, it attempts to link empowering leadership to creativity from the perspective of information processing, which is different from traditional mechanisms of psychology. Design/methodology/approach: Based on the perspective of information processing, the authors tested how and why different levels of empowering leadership may relate to team and individual creativity. Multi-source data were collected from 62 team leaders and 295 team members. Statistical methods, such as the hierarchical linear model, hierarchical regression analysis, and bootstrapping tests, were used to analyze the data. Findings: The results show that team and individual learning mediate the effects of empowering leadership on creativity at the team and individual levels. Interestingly, the authors also found that team learning negatively moderates the indirect and positive effect of individual empowering leadership on individual creativity. Research limitations/implications: The main limitation of this study is that the authors used cross-section data instead of longitudinal data to analyze the causal relationship. As such, the results may not truly reveal the causality. Practical implications: The findings indicate that empowering leadership is important for stimulating both individual and team learning; thus, it benefits different levels of creativity. In addition, the results also suggest that there are interplay between different level mechanisms, and empowering team leader should trade-off individual and team learning effects in order to promote both team and individual creativity effectively. Originality/value: This study contributes to the existing literature by providing a multi-level and cross-level analysis of empowering leadership and creativity. It clarifies how empowering leadership stimulates individual and team creativity at different levels simultaneously.